초등교과서 연산 단원에서의 계산어림 지도 내용에 대한 고찰 - 권성룡 (한국초등수학교육학회지, 24(1), 2020)
본 연구는 초등학교 수학에서의 계산어림활동을 고찰함으로써 계산어림지도를 위한 개선방향을 모색하고자 2015 개정 초등학교 수학과 교육과정과 그에 따른 수학교과서 및 교사용지도서에 포함된 계산어림 관련 내용을 살펴보았다. 이를 통해서 전학년군에 걸쳐서 계산어림을 강조할 필요가 있으며, 계산어림의 효과적인 지도를 위해서 계산어림하기, 어림과정설명하기, 어림값과 계산값 비교를 통한 계산결과의 타당성 검증하기 등을 체계적으로 지도하는 것이 필요하며, 연산관련단원에서 계산어림관련 활동을 좀 더 강화하는 것이 필요하다는 것을 알 수 있었다. The purpose of this study was to find a future direction for improving computational estimation instruction through examining the contents of computational estimation included in the 2015 revised elementary school mathematics curriculum and elementary school mathematics textbook and teacher's guide. Through this, several suggestions was made as follow. Firs, it is necessary to emphasize the computational estimation across all grade groups. Second, it is necessary to teach the computational estimation strategies systematically. It was found that it is necessary to reinforce the activities related to computational estimation in the computation related units. KCI Citation Count: 0